Genetic alterations related to BRAF‐FGFR genes and dysregulated MAPK/ERK/mTOR signaling in adult pilocytic astrocytoma. (6th January 2017) - Pathak, Pankaj; Kumar, Anupam; Jha, Prerana; Purkait, Suvendu; Faruq, Mohammed; Suri, Ashish; Suri, Vaishali; Sharma, Mehar C.; Sarkar, Chitra
Abstract: Pilocytic astrocytomas occur rarely in adults and show aggressive tumor behavior. However, their underlying molecular‐genetic events are largely uncharacterized. Hence, 59 adult pilocytic astrocytoma (APA) cases of classical histology were studied (MIB‐1 LI: 1%–5%). Analysis of BRAF alterations using qRT‐PCR, confirmed KIAA1549‐BRAF fusion in 11 (19%) and BRAF‐gain in 2 (3.4%) cases. BRAF‐V600E mutation was noted in 1 (1.7%) case by sequencing. FGFR1‐mutation and FGFR‐TKD duplication were seen in 7/59 (11.9%) and 3/59 (5%) cases, respectively. Overall 36% of APAs harbored BRAF and/or FGFR genetic alterations. Notably, FGFR related genetic alterations were enriched in tumors of supratentorial region (8/25, 32%) as compared with other locations ( P  = 0.01). The difference in age of cases with FGFR1‐mutation (Mean age ± SD: 37.2 ± 15 years) vs. KIAA1549‐BRAF fusion (Mean age ± SD: 25.1 ± 4.1 years) was statistically significant ( P  = 0.03). Combined BRAF and FGFR alterations were identified in 3 (5%) cases. Notably, the cases with more than one genetic alteration were in higher age group (Mean age ± SD: 50 ± 12 years) as compared with cases with single genetic alteration (Mean age ± SD: 29 ± 10; P  = 0.003). Immunopositivity of p‐MAPK/p‐MEK1 was found in all the cases examined. The pS6‐immunoreactivity, a marker of mTOR activation was observed in 34/39 (87%) cases. Interestingly, cases with BRAF and/or FGFR related alteration showed significantly lower pS6‐immunostatining (3/12; 25%) as compared with those with wild‐type BRAF and/or FGFR (16/27; 59%) ( P  = 0.04). Further, analysis of seven IDH wild‐type adult diffuse astrocytomas (DA) showed FGFR related genetic alterations in 43% cases. These and previous results suggest that APAs are genetically similar to IDH wild‐type adult DAs. APAs harbor infrequent BRAF alterations but more frequent FGFR alterations as compared with pediatric cases. KIAA1549‐BRAF fusion inversely correlates with increasing age whereas FGFR1‐mutation associates with older age. Activation of MAPK/ERK/mTOR signaling appears to be an important oncogenic event in APAs and may be underlying event of aggressive tumor behavior. The findings provided a rationale for potential therapeutic advantage of targeting MAPK/ERK/mTOR pathway in APAs.